O ENTRE-LUGAR DO DESENHO CONTEMPORÂNEO: Processo-fatura (Palíndromo, 2013)
The text presents problematizations from the drawing theme in order to bring to debate drawing as fragment-idea and the implications of this feature in contemporary art  where everything can be legitimized by a prolix rhetoric of structured discourse in contributive way stoun certain ties, extolling the excesses and fragilities within the arts.
Keywords: drawing; art; excess; discourse